Shear Behavior of Two-Layer Beams Made of Normal and Lightweight Concrete Layers - AL-Farttoosi, Hayder Kadhem Adai; Abdulrazzaq, Oday A.; Hussain, Haleem K. (Basrah Journal for Engineering Sciences, 2022)
This study investigates the shear strength behavior of two-layer reinforced concrete beams consisting of two different types of concrete. One of the layers made of lightweight concrete (LWC) and the other was normal weight concrete (NWC). A total of 16 shear deficient reinforced concrete beams were fabricated and cast with NWC, LWC, and two-layer beam of both material with different configuration. All the beams were tested under four-point loading after 28 days. The variables of the experimental program include the ratio of thickness of the lightweight concrete layer to the overall depth of beam ( h LW / h ), and concrete compressive strength. Experimental results which include load-deflection response curves along with failure modes for NWC, LWC and two-layer beams. The results showed that all beams failed in a similar mode, due to diagonal tension shear crack. Based on the experimental results it can be also concluded that the shear load is governed by compressive strength of lower layer of the concrete when the shear span to overall depth ( a / h ) of the beams is 2.75 or more. While for the a / h 2.375 and 2.00 the two-layer beam has a significant reduction in the shear capacity compared to the NWC beams and increasing compared to LWC beam. The ratio of experimental shear stress divided by the root square of concrete compressive strength (vexp √f c ' ) , which demonstrates the diagonally cracked concrete's ability to transfer strain and shear was maintained for all configurations greater than 0.17, which is the minimal value recommended by ACI318-19.